Organotrialkoxysilanes Mediate the Syntheses of Fluorescent Gold Nanoparticles and TiO2-Supported Ag−Ni Nanocatalysts for Selective Hydrazine Sensing and Decomposition - Mitra M.D.; Singh H.; Singh R.; Pandey P.C. (My University, 2025)
Organotrialkoxysilanes enabled the controlled synthesis of mono-metallic and bimetallic noble metal nanoparticles. 3-Aminopropyltrimethoxysilane (3-APTMS)-treated gold cations were quickly (1 minute) transformed into gold nanoparticles (AuNPs) in the presence of 3-glycidoxypropyltrimethoxysilane (3-GPTMS). As made AuNPs demonstrated exceptional fluorescence properties with 15 % QY, and the blue fluorescence of nanomaterials is supported by CIE coordinates. Fluorescent gold nanoparticles were evaluated using UV- Visible spectroscopy, X-ray photoelectron spectroscopy (XPS), zeta potential, X-ray diffraction (XRD), fluorescence spectroscopy (FL), and transmission electron microscopy (TEM), mediated by the use of organotrialkoxysilanes, gold nanoparticles with an average particle size of 4–8 nm were produced, which could be helpful for the direct determination of hydrazine via fluorescence spectroscopy. The detection limit for hydrous hydrazine is 0.047 μM, with a linear range of 0.1–1 μM (R2=0.995). In addition, organotrialkoxysilanes were also used as templates for the stabilization and formation of supported TiO2 bimetallic Ag−Ni nanoparticles for use as photo-nanocatalysts. TiO2-supported bimetallic Ag−Ni nanocatalyst were characterized by field emission scanning electron microscope (FE SEM), EDX, elemental mapping, and the Brunauer-Emmett-Teller (BET) technique. Real-time hydrazine decomposition was enabled by the as-built heterogeneous support in the presence of sunlight. © 2023 Wiley-VCH GmbH.